Telehealth for Addressing Sexual and Reproductive Health and Rights Needs During the COVID-19 Pandemic and Beyond: A Hybrid Telemedicine-Community Accompaniment Model for Abortion and Contraception Services in Pakistan - Shaikh, Irum; Küng, Stephanie Andrea; Aziz, Hina; Sabir, Samina; Shabbir, Ghulam; Ahmed, Mukhtar; Dabash, Rasha (Frontiers in Global Women's Health, 2021)
The COVID-19 pandemic has and continues to devastate health systems. In an effort to meet growing needs with limited resources, it has led overburdened healthcare systems to deprioritize essential sexual and reproductive healthcare, including abortion and contraception care, leaving many people with no recourse for preventing or terminating pregnancies. The pandemic simultaneously accelerated shifts in healthcare delivery that had already begun to seed, drawing on digital technologies to create reach and access that were once assumed to be too difficult or impossible to implement in many settings. In order to respond to sexual and reproductive health and rights (SRHR) needs in the context of the COVID-19 pandemic and to overcome the digital divide’s impact on telemedicine access, Ipas Pakistan launched a novel hybrid telemedicine-community accompaniment pilot in June 2020. Ipas partnered with Sehat Kahani (SK), a local healthcare NGO and telehealth service, and an existing network of Lady Health Workers (LHWs). Ipas adapted its abortion training to virtually train 98 LHWs and 22 telehealth providers. The model facilitated linking women via LHWs with mobile devices to online providers for telemedicine consultations for SRH, including abortion services, contraception, and other gynecological consults. Data collected during the pilot shows that provision of SRHR services via a telehealth-accompaniment model can be successfully implemented in Pakistan and show promising preliminary results in being able to bridge the digital divide. Outcome data shows high satisfaction and good clinical outcomes for women accessing care through this model. However, more data are needed to understand the model’s full potential. Barriers to digital health models in settings like Pakistan remain, such as poor or inconsistent internet access, especially in rural settings. This approach has its limitations but should be considered as an option in settings with similarly established community health networks and inequitable access to digital health.